2015
DOI: 10.1177/1545968315624979
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Motor Recovery After Stroke With Combined Cortical Stimulation and Rehabilitative Training Is Dependent on Infarct Location

Abstract: Background Cortical electrical stimulation of motor cortex in combination with rehabilitative training (CS/RT) has been shown to enhance motor recovery in animal models of focal cortical stroke yet in clinical trials the effects are much less robust. The variability of stroke location in human patient populations that include both cortical and subcortical brain regions may contribute to the failure to find consistent effects clinically. Objective This study sought to determine whether infarct location influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In addition, we used implantable electrical stimulator which can stimulate rats continuously and allow rats to move freely in their home cages. A combination of electrical stimulation and rehabilitation is thought to augment these endogenous plasticity processes [45, 46]. Therefore, rats may have showed more amelioration of motor function due to the merit of stimulation system used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we used implantable electrical stimulator which can stimulate rats continuously and allow rats to move freely in their home cages. A combination of electrical stimulation and rehabilitation is thought to augment these endogenous plasticity processes [45, 46]. Therefore, rats may have showed more amelioration of motor function due to the merit of stimulation system used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a single subcortical white matter damage would result in cortical differentiation causing widespread cortical dysfunction or severe motor impairment and poor motor recovery [63,64]. Hence, when evaluating the effect of fMV/WBV on post-stroke recovery, it should be taken into account that the efficacy would depend on the specific pattern of brain damage [62]. Only a few sporadic case series have been carried out specifically on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating balance before and after WBV found no beneficial effect in chronic stroke patients [59]. Similarly, measures of clinical functional evaluation in chronic stroke patients such as the 6 Minute Walking Test [60,61], Timed Up and Go test [57], and Berg Balance Scale [62] revealed non-significant effects of WBV. Concerning the exact timing of clinical, neurophysiological, or behavioral evaluations before and after WBV, many studies have made the evaluation before and soon after WBV [54,[57][58][59]61] or at 1 month [56, 60] and 6 weeks following WBV [55].…”
Section: Wbv In Chronic Strokementioning
confidence: 99%
“…The anatomical region that is injured is also thought to be associated with this result [55]. In other words, it has been hypothesized that corticospinal tract integrity is essential for CS to have an effect.…”
Section: Epidural Cortical Stimulation (Cs)mentioning
confidence: 99%